Sosialisasi Moderasi Beragama di GMIT Zoar Penkase - Nofita Rudiani Asbanu; Saniria Benu; Neti Saekoko; Claudina Margarida Freitas Belo; Barbara Green Winsle Bessie; Ivony Welchristin Adelis Oematan; Salomi Poko; Harun Yeremia Natonis; Anita Adriance Hege Udju (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service (PKM) activity conducted by the Master's Program in Christian Religious Education at GMIT Zoar Penkase addressed the theme